2009
DOI: 10.1071/wr08018
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of euthanasia and trap - neuter - return (TNR) programs in managing free-roaming cat populations

Abstract: Global estimates of the number of domestic cats (Felis catus) are >400 million. Issues associated with freeroaming cats are of global importance because of animal-welfare and public-health concerns and impacts on native wildlife through predation, competition and disease transmission. In the United States, proposed control solutions for managing urban free-roaming cat populations include euthanasia and trap-neuter-return (TNR) programs. We evaluated control methods using a demographic population model for a 25… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
57
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(57 citation statements)
references
References 26 publications
0
57
0
Order By: Relevance
“…High survival rate may indicate that feeding programs result in healthier and safer populations who are less at risk from trauma, disease, and starvation. Population models show that sterilization needs to exceed 50% (Schmidt et al, 2009) to 75% (Andersen et al, 2004) to effectively reduce cat populations, and even higher rates are needed to offset immigration.…”
Section: Sterilization Effectmentioning
confidence: 99%
See 1 more Smart Citation
“…High survival rate may indicate that feeding programs result in healthier and safer populations who are less at risk from trauma, disease, and starvation. Population models show that sterilization needs to exceed 50% (Schmidt et al, 2009) to 75% (Andersen et al, 2004) to effectively reduce cat populations, and even higher rates are needed to offset immigration.…”
Section: Sterilization Effectmentioning
confidence: 99%
“…Cat caretakers also reported a low immigration rate at the monitored colonies. Feeding programs may reduce competitive behavior for resources (Levy et al, 2003), increase carrying capacity, and lead to increased immigration (Schmidt et al, 2009); perhaps there are other factors explaining the low immigration rate. Cat caretakers' food was mostly eaten directly at feeding times with the remainder very well hidden.…”
Section: Population Sizementioning
confidence: 99%
“…The study emphasized the need for scientific information to evaluate the effectiveness of this growing management method. The effectiveness of TNR programs on reducing cat populations has been found to be successful (Levy, Gale, & Gale, ; Lohr, Cox, & Lepczyk, ; Schmidt, Swannack, Lopez, & Slater, ). Trap‐euthanize programs are more effective at reducing colony size than TNR (Andersen, Martin, & Roemer, ; Lohr et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Trap‐euthanize programs are more effective at reducing colony size than TNR (Andersen, Martin, & Roemer, ; Lohr et al, ). However, Schmidt et al () found that both methods were comparable as long as treatment rates were greater than 50%. Domestic cat abandonment needs to be reduced for either method to be effective (Lohr et al, ; Schmidt et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, a contraceptive treatment need not be effective in each animal, but a predictable effect at the population level is required. Most cat control models suggest that approximately 70–80% of female cats in a population must be rendered infertile to induce a decline in population size 2225…”
Section: Introductionmentioning
confidence: 99%